Determination of genetic variation of Rhanterium epapposum in Kuwait desert using RAPD and SRAP DNA-based markers - Al-SALAMEEN, F.; Al-AMAD, S.; Al-HASHASH, H. (Kuwait Journal of Science, 2014)
Rhanterium epapposum (R. epapposum) Olive is a perennial shrub found in the northern part of Kuwait with unique climate and land conditions such as drought and salt tolerance. Due to several reasons, this species is on the verge of extinction. R. epapposum is one of the desert forage plants upon which camel and sheep graze. Bedouins also use R. epapposum as a source of fuel. Thus, it is necessary to evaluate the genetic diversity within and among population of germplasm to determine and understand the extent of genetic variation that exists in the species. This evaluation was performed in an effort to reduce or stop the genetic erosion. Twenty-four Random Amplified Polymorphic DNA (RAPD) and 23 Sequence Related Amplified Polymorphisms (SRAPs) markers were used to amplify DNA fragments from 18 different samples collected from five major locations in Kuwait. Results indicated that there were 64 alleles produced by RAPD, while 129 alleles were produced by SRAP. With slightly different samples in each cluster, the cultivars were grouped into four distinct clusters by coefficients of similarity that were generated with RAPD, SRAP, and the combined data of both. With the absence of any pedigree information, this study indicated that these DNA-based markers could be used to obtain efficient, accurate, and high throughput fingerprinting, revealing significant variation among the existing locations that can be explored in order to preserve the species.